ANALISIS MANAJEMEN PESERTA DIDIK DI SEKOLAH DASAR NEGERI 130/IV KOTA JAMBI - Aris Munandar; M Sholihin; Bella Salsabila; Nabila Inasari; Husnul Khotimah; Julia Aurel Zabadiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of student management at SDN 130/VI Jambi City, which includes the processes of habituation, discipline, supervision, teacher evaluation, and the mechanism for new student admissions. The study uses a qualitative method with a descriptive approach, where data is collected through interviews, observations, and documentation. The results show that the school implements character habituation through routine activities such as flag ceremonies, literacy programs, morning exercises, and Yasin readings as efforts to shape students' character. Discipline supervision is conducted through the formation of the Anti-Bullying and Discipline Team, as well as collaboration between homeroom teachers and parents. The teacher supervision system also works effectively to evaluate educational services while monitoring both academic and non-academic student development. Additionally, extracurricular activities have a positive impact on student achievement at the national level. The student admission process.